Candida pneumonia with severe clinical course, recovery with antifungal therapy and unusual pathologic findings: A case report. Issue 2 (January 2018) - Dermawan, Josephine Kam Tai; Ghosh, Subha; Keating, M. Kelly; Gopalakrishna, K.V.; Mukhopadhyay, Sanjay
Abstract: Background: Candida is frequently isolated from the respiratory tract and usually reflects airway colonization. True Candida pneumonia is rare. Our aim is to document a case of Candida pneumonia confirmed by cultures, molecular techniques, and surgical lung biopsy, and to highlight a previously unreported pathologic manifestation of this infection. Case summary: A 59-year-old man with a history of chronic obstructive pulmonary disease (COPD) presented with dry cough, low-grade fever, and progressive dyspnea. He was eventually diagnosed with sarcoidosis based on bilateral lung infiltrates and granulomas in a transbronchial biopsy. His condition worsened after immunosuppression, prompting surgical lung biopsy, which revealed suppurative granulomas containing Candida albicans, confirmed by cultures and polymerase chain reaction. Despite multiple episodes of respiratory failure and a prolonged course in intensive care, he recovered fully after antifungal therapy and is currently alive with COPD-related dyspnea 3 years after his initial presentation. Conclusion: Candida can rarely cause clinically significant pneumonia in adults, and should be considered in the differential diagnosis of suppurative granulomas in the lung.